Penggunaan Internet Sebagai Media Pembelajaran Pada Pelajaran Seni Budaya (Musik) Di Kelas X SMK Negeri 4 Kerinci - Andra Yoneska; Yos Sudarman (FBS Universitas Negeri Padang, 2020)
This study aims to explain the use of the internet as a learning media in Culture and Arts (music) instruction in grade X of SMK Negeri 4 Kerinci. The research problem stems from the existence of internet facilities in the school, but the use has not been on target. This study belongs to qualitative research with a descriptive analysis approach. The object of research was the learning activity of Culture and Arts (music) by using the internet which was conducted in grade X of SMK Negeri 4 Kerinci. The research instruments were observation, interview, and document study. Meanwhile, the data were collected through documentation notes, field notes, and interview guides. Moreover, the data were analyzed by using a qualitative descriptive approach. The results of the study explain that the use of the internet as a learning media in Culture and Arts (music) instruction in grade X of SMK Negeri 4 Kerinci has resulted in inappropriate internet usage. Learning activities that should be guided more by teachers in class are often left to students for internet-facilitated learning. Due to the fact that students get assignments to seek knowledge and understanding via the internet, the teacher often do not attend the class. The teachers let students learn Culture and Arts in the classroom using the internet without teachers’ guidance. As a result, the students do their assignments improperly. The internet is mostly used by students for things which are not really related to the subject learned. This can be proven from the fact that when the teacher asks questions and gives tests at the next meeting, the students cannot answer properly and correctly.